VISUAL AND VERBAL CREATIVITY IN ENGLISH TEACHING FOR ENGLISH LEARNERS: A STUDY OF YOUTUBE CHANNELS (INTERNATIONAL SEMINAR, 2024)
This study aims to analyze visual and verbal creativity in English teaching content on YouTube channels. Using a qualitative approach, it examines visual elements such as animation, graphics, and text, alongside verbal techniques including storytelling, humor, and intonation variation employed by content creators in educational videos. Content analysis was conducted by identifying and categorizing these elements across several popular YouTube channels focusing on English language teaching. The findings reveal that visual aids, such as flashcards and photos, help learners connect English vocabulary with real-life contexts, making abstract concepts tangible and enhancing comprehension. Verbal elements, including clear instructions, storytelling, and humor, engage learners and reduce anxiety, fostering a motivating environment. Rachel’s English emphasizes interactive tasks supported by visuals, while Tiffany’s channel employs structured steps to encourage consistent practice and fluency building. Both channels demonstrate how verbal and visual elements complement each other to enhance learners' understanding and engagement. This study highlights the significance of integrating visual and verbal creativity in digital media to facilitate effective English learning and offers recommendations for content creators and educators to improve the quality of digital teaching materials.